«Tamen moratur in urbe continue». Alfonso di Jaén, un eremita di città (Roma, Perugia, Genova) - Nocentini, Silvia (Rivista di storia della Chiesa in Italia, 2024)
Based on unedited documents, this work outlines some unexplored sides of the life of Alfonso of Jaén (1330-1389), confessor and editor of Saint Birgitta of Sweden. Under Gregory XI’s and Urban VI’s papacy, he also served as a curialist and, following Birgitta’s death, reformer of monastic communities and organizer of the Birgittine propaganda. In the earliest times of the Great Schism, his figure must be considered prominent and influential for several religious and lay actors. An Appendix follows with the edition of a letter from Gregory XI, the deposition of Alfonso in an inquest on the election of Urban VI, a letter from the apostolic penitentiary Luca Ridolfucci, and the inscription on Alfonso’s tomb.